2022
DOI: 10.1101/2022.05.28.493830
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Single-cell perspectives on the function and development of deep-sea mussel bacteriocytes

Abstract: Symbiosis is known to be a major force driving the adaptation and evolution of multicellular organisms. The symbiotic cells and organs, on the meantime, directly provide the mutualist services to the host as the source of phenotypic complexity and outcome of development plasticity. The investigations on the formation and development of symbiotic cells and organs however still remain a challenge in both model and non-model holobionts. Here, by constructing the high-resolution single-cell expression atlas of gil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Moreover, the differential expression of the sterol-related signaling pathway under methane deprivation might be a cascade reaction triggered by the shortage of symbiont-deprived sterol intermediates 37 . In support of this speculation, data from the single-cell transcriptome analysis also suggested that the methanotrophic symbionts could influence the differentiation and maturation processes of bacteriocytes via the sterol-related signaling pathway 43 . It is also noticeable that majority of animal hosts have formed coordinated sterol metabolism with their symbionts, highlighting the possible role of sterol-related signaling pathway in the phenotypic plasticity of symbiotic cells and organs across different holobionts.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Moreover, the differential expression of the sterol-related signaling pathway under methane deprivation might be a cascade reaction triggered by the shortage of symbiont-deprived sterol intermediates 37 . In support of this speculation, data from the single-cell transcriptome analysis also suggested that the methanotrophic symbionts could influence the differentiation and maturation processes of bacteriocytes via the sterol-related signaling pathway 43 . It is also noticeable that majority of animal hosts have formed coordinated sterol metabolism with their symbionts, highlighting the possible role of sterol-related signaling pathway in the phenotypic plasticity of symbiotic cells and organs across different holobionts.…”
Section: Discussionmentioning
confidence: 81%
“…Therefore, phenotypic changes in symbiotic cells and organs can occur frequently in part or in whole for deep-sea mussels regarding to the intensity of environmental change and serve as key indicators of deep-sea mining or other anthropogenic activities. Besides, the deep-sea mussel could survive even much longer than one year in natural condition since our experimental condition is much harsh 31,43 . While the phenotypic changes of the digestion system remain unexplored, the long-term survival of deep-sea mussels under methane deprivation might also endow them with transgenerational effects, allowing for a permanent transition from chemoautotrophy (a symbiotic association with thiotrophs) or chemoheterotrophy (a symbiotic association with methanotrophs) to strict heterotrophy (filter-feeding).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was demonstrated that bacteriocytes could retrieve fructose-6-phosphate (F6P) directly from methanotrophic symbionts by sugar phosphate exchanger genes and convert it into glucose-6-phosphate (G6P), fructose-1,6-bisphosphate (F-1,6-BP) and glyceraldehyde-3-phosphate (G6P) before redistributing them back to both the host and symbionts as supplements of gluconeogenesis and the tricarboxylic acid cycle (TCA cycle). A direct supply of ammonia from the host to symbionts via ammonium transporters was also reported (Chen et al 2022). The bioconversion and exchange of sugar phosphate and ammonia between the host and symbionts provided an efficient and direct way to coordinate the metabolism of both partners, which greatly promoted the efficiency and profits of symbiosis.…”
Section: Nutrient Transfer Between Host and Symbiontsmentioning
confidence: 89%